2001
DOI: 10.1034/j.1600-0773.2001.880608.x
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Quantitative Risk Assessment of Non‐Threshold Carcinogens Based on the Dose Descriptor T25

Abstract: This report provides guidance for using the dose-descriptor T25 from animal studies as a basis for quantitative risk characterisation of non-threshold carcinogens. T25 is presently used within the European Union for setting specific concentration limits for carcinogens in relation to labelling of preparations (formulations). The T25 is defined as the chronic dose rate which will give 25% of the animals tumours at a specific tissue site, after correction for spontaneous incidence, within the standard life-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 4 publications
3
24
0
1
Order By: Relevance
“…Previously, it has been observed that the dose descriptor T25 gives very similar results as the dose descriptor TD50. Moreover, hazard characterization based on T25 gives results that are in good agreement with results based on the linearised multistage model and the benchmark method using LED 10 (Sanner et al 2001). Recently, a good agreement has been observed between hazard characterization based on animal studies using the T25 method and epidemiological studies (Sanner & Dybing 2005).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Previously, it has been observed that the dose descriptor T25 gives very similar results as the dose descriptor TD50. Moreover, hazard characterization based on T25 gives results that are in good agreement with results based on the linearised multistage model and the benchmark method using LED 10 (Sanner et al 2001). Recently, a good agreement has been observed between hazard characterization based on animal studies using the T25 method and epidemiological studies (Sanner & Dybing 2005).…”
Section: Discussionsupporting
confidence: 66%
“…The T25 method is used within EU in setting specific concentration limits for carcinogens in preparations (EC 1999) and this method for quantitative hazard assessment of non-threshold carcinogens (Sanner et al 2001) is presently used in several regulatory areas within EU (e.g. SCCNFP 2003).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…a certain percentage tumour incidence) within but towards the lower end of the doseresponse curve, that is derived by fitting a mathematical model to the data (Lovell and Thomas, 1996;Dybing et al, 1997;Sanner et al, 2001;Van Landingham et al, 2001). The fixed response can be used directly to produce advice that allows comparisons to be made between different compounds producing the same response in the same species and strain of animals.…”
Section: Threshold Approaches In Hazard Characterisationmentioning
confidence: 99%